Haematobiochemical changes of ovine (Ovis aries) blood during storage for transfusion (Research in Agriculture Livestock and Fisheries, 2020)
Haematobiochemical changes of ovine (sheep) blood were investigated during preservation and storage with Citrate Phosphate Dextrose Adenine-1 (CPDA-1) and Acid Citrate Dextrose (ACD) for transfusion. Twelve healthy sheep were selected and divided into two equal groups: group X (n=6) and group Y (n=6). Thirty-five ml of blood was collected from each animal and preserved with CPDA-1 in group X and ACD in group Y under 4°C in refrigerator for 28 days. Haematological changes viz., total erythrocyte count (TEC), total leukocyte count (TLC), haemoglobin (Hb), packed cell volume (PCV), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC); and biochemical changes viz., total protein (TP) and pH were evaluated immediately after blood collection and thereafter on day-1, day-3, day-7, day-14, day-21 and day-28 for both groups. In ACD preserved blood; TEC, TLC, Hb and PCV decreased significantly (P